Indoor and outdoor air pollutants relationship at primary schools in Kuala Terengganu - Nur Zafirah Mohd Sofian (Fakulti Sains dan Teknologi, 2012)
Studies have found that indoor air quality affects human especially children and the elderly more compared to ambient air. This study aims to determine the concentration of respirable suspended particulate matter, carbon monoxide and carbon dioxide in selected primary schools with different surrounding human activities; assess the measured concentrations compliance with existing IAQ guidelines and standards; and to establish statistical relationships between indoor and outdoor air pollutant concentrations in each selected schools in Kuala Terengganu.